MES guide for executives : why and how to select, implement, and maintain a manufacturing execution system. - Scholten, Bianca, ....- ([s.l.] : ISA, 2009)
Are you having trouble demonstrating to management what a manufacturing execution system (MES) is and what it can do for you? Or do you simply need to justify why your company even needs an MES? Perhaps you're the executive decision maker and just need some answers. Bianca Scholten, author of the best-selling book The Road to Integration: A Guide to Applying ISA-95 in Manufacturing, shares her expertise on the topic in this easy-to-read guide to MES. In recent decades, industrial companies have invested much time and money in not only machine and production line automation but also ERP (Enterprise Resource Planning) systems. The MES falls between these two layers. Many plants rely on outdated methods for both preparatory activities (such as detailed production scheduling and recipe management) and retrospective activities (such as data collection, reporting, and analysis). MES can provide an effective remedy to this time-consuming, error-prone situation. Ideal for CEOs, CFOs, and managers, Scholten's book sheds light on how to complete your plant's move into the twenty-first century. Using knowledge gleaned from her extensive experience as an MES consultant and from IT professionals, production managers, and colleagues who have been through the MES experience, Scholten covers MES selection, what to expect during implementation and initial use, the advantages of using a single MES for multiple sites (and how to develop one), and return on investment considerations. She also provides a bird's-eye view of the widely adopted ISA-95 standard to facilitate effective, efficient communication between company systems.